Detection of Hepatitis -B virus Genotypes among Chronic Carriers in Duhok - Iraq - Abdulla, Ibrahim M.; Goreal, Amer Abdalla (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Hepatitis B virus (HBV) is one of the major etiological agents causing acute and chronic liver disease worldwide with significant morbidity and mortality. The high genetic variability of HBV is reflected by eight genotypes (A to H), each with a particular geographical prevalence. Objectives: The study was conducted to find out HBV genotypes in chronic hepatitis B- (CHB) carriers in association with serological markers of HBV. Methods: This work was carried on from March to, December 2012 in Duhok/Iraq and enrolled 134 HBsAg positive carrier cases. recruited to Central Public Health Lab. Specific primers PCR technique was used to detect HBV genotypes. The carrier cases were screened for markers of HBV infection by Enzyme Linked Immunosorbent Assay (ELISA). Automated machine for quantitative determination of ALT was used. Results: The carrier cases were 91 males (67.9 %), 43 females (32.1 %), and their age range was 10-87 year old (mean=31.4 SD± 13.3). Among the studied patients 133(99.2%) were found to have genotypes D including 91(67.9%) males and 42(31.3%) females and only one female patient carried genotype B (0.8%). Anti-HBc(total), IgM anti-HBc, HBeAg and Anti HBeAb were detected in rates of 100%,0%,50%and 46.9 % respectively. The patient with genotype B had positive HBe Ag, negative HBeAb and normal ALT level. Conclusion: This study revealed that hepatitis B virus genotype D is the main genotype in Duhok/ Iraq followed by genotype B. High percentage of CHB patients with genotype D are HBeAg positive. Most of CHB patients with high ALT level had positive HBeAg rather than negative HBeAg.